GAMBARAN JUMLAH SKS MATA KULIAH PERGURUAN TINGGI FARMASI INDONESIA YANG MENDUKUNG PENGGUNAAN OBAT YANG RASIONAL - Hendy Ristiono; Sri Suryawati; Sulanto Saleh Danu (Universitas Ahmad Dahlan, 2015)
According to World Â Health Organization (WHO), there are two major steps as a commitment to make changes in the implementation of pharmacy practice that are national drug policy and learning system changes in pharmacy education. The aim of the research was to obtain the cummulative credit overview in college of pharmacy in Indonesia that supporting Rational Drug Use based on promotion rational drug use (PRDU) and International network Â rational use of drug (INRUD). This study used a analytic descriptive design. The study was located in some colleges of pharmacy in Indonesia. Data was collected through observation of the recent curriculum used in the Indonesian college of pharmacy. Research were conducted by giving a questionnaire on the rational drug use topic in the curriculum and in-depth interviews with the dean or faculties appointed by the dean. The number of credits developed by 21 colleges of pharmacy as respondents have in between 140-158 credits. Median number of credits developed by C accreditation level are more than A and B accreditation level. Three ofÂ A accreditation level of colleges have number of credits in between 66-171 credits and a college with B accreditation level as much as 36.9 credits. Whereas in total of credits semester that support the RDU in Community and Clinical Pharmacy (CCP) interests has more than the non-CCP interests.